EKONOMI SIRKULAR DI PESANTREN: INOVASI PP. ANNUQAYAH LUBANGSA DALAM PENGELOLAAN SAMPAH - Amin, Moh. Abqoriyin; Maksum, Maksum; Muktirrahman, Muktirrahman; Huda, Nurul (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This research aims to explore the application of circular economy principles in pesantren through a case study of the waste management system of PP. Annuqayah Lubangsa. Using a descriptive qualitative approach, data was collected through participant observation, semi-structured interviews with 15 key informants, and document analysis. The results showed that PP. Annuqayah Lubangsa has successfully developed a sustainable waste management system through the Jatian Technical Implementation Unit (UPT). The circular economy model implemented includes systematic waste segregation into plastic, paper, organic, and residue categories, followed by value-added processing that generates a monthly income of IDR 3 to 3.5 million. The research identified three key success factors: community-based management involving santri in the entire process, integration of Islamic ecological ethics, and development of innovative products such as plastic paving blocks. This research contributes to the understanding of how religious educational institutions can simultaneously address waste management challenges, create economic value and support environmental sustainability, and offers a replicable model for similar institutions. Research limitations include the focus on a single case study and the use of qualitative metrics for economic impact assessment.